2019
DOI: 10.2147/ott.s193937
|View full text |Cite
|
Sign up to set email alerts
|

<p>miR-495-3p inhibits the cell proliferation, invasion and migration of osteosarcoma by targeting C1q/TNF-related protein 3</p>

Abstract: Background: Osteosarcoma (OS) is one of the most common malignant tumors of bone, and microRNAs (miRNAs/miRs) serve critical roles in the progression of human OS. The aim of the present study was to investigate the role of miR-495-3p in OS. Methods: The expression of miR-495-3p in OS tissues and adjacent tissues from 30 patients was measured by reverse transcription-quantitative PCR (RT-qPCR). Human OS cell lines (U-2 OS, MG-63 and Saos-2 cells) and normal osteopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…It has been reported that miR-495-3p participates in the regulation of tumor cell bioactivity. For example, miR-495-3p regulates osteosarcoma cell apoptosis by targeting C1q/TNF-related protein 3 (32). To investigate the roles of miR-495-3p in CRC cell proliferation, miR-495-3p was effectively overexpressed in the SW480 and LoVo cells (P<0.01; Fig.…”
Section: Mir-495-3p Overexpression Inhibits Crc Cell Proliferation Mmentioning
confidence: 95%
“…It has been reported that miR-495-3p participates in the regulation of tumor cell bioactivity. For example, miR-495-3p regulates osteosarcoma cell apoptosis by targeting C1q/TNF-related protein 3 (32). To investigate the roles of miR-495-3p in CRC cell proliferation, miR-495-3p was effectively overexpressed in the SW480 and LoVo cells (P<0.01; Fig.…”
Section: Mir-495-3p Overexpression Inhibits Crc Cell Proliferation Mmentioning
confidence: 95%
“…MiR-495-3p was revealed to exert a suppressive role in a range of cancers. One report revealed that miR-495-3p upregulation could repress cell migration, invasion, and proliferation in osteosarcoma cells [18]. Wang et al reported that lncRNA LUCAT1 depletion increased miR-495-3p expression in clear cell renal cell cancer cells, which could suppress cancer cell [35].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, miRNAs are revealed to be abnormally expressed in tumors and have attracted widespread attention [15]. MicroRNA-495-3p (miR-495-3p) was showed to be downregulated in a series of tumors, such as colon cancer [16], melanoma [17], and osteosarcoma [18]. MiR-495-3p served as a suppressor in gastric carcinogenesis via modulating multiple epigenetic modifiers [19].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the relative stability of miRNA expression, some studies have used miRNAs as biomarkers [28]. Recent studies have found that miR-495 was involved in the tumorigenesis and progression of various cancers, including lung cancer [11], nasopharyngeal carcinoma [29], osteosarcoma [30], and melanoma [31]. All of these studies have identified miR-495 as a tumor suppressor.…”
Section: Il-11 Rescues the Inhibition Of Cell Proliferation Mediated mentioning
confidence: 99%